Respuesta :
option A i.e. Three-fourths (four-thirds) x = negative 6 (four-thirds).
Step-by-step explanation:
We have , The given expression as Three-fourths x = negative 6 , which can be written as [tex]\frac{3}{4} (x) = -6[/tex] . Now in order to solve this equation in one step , we must notice that coefficient of x must be 1 but it's [tex]\frac{3}{4}[/tex] , Let's make coefficient of x as 1 by multiplying both side of equations by 4/3:
[tex]\frac{3}{4} (x) = -6[/tex]
⇒ [tex]\frac{3}{4} (x) = -6[/tex]
⇒ [tex]\frac{3}{4}(\frac{4}{3} ) (x) = -6(\frac{4}{3} )[/tex]
⇒ [tex]x = -6(\frac{4}{3} )[/tex]
⇒ [tex]x = -2(4)[/tex]
⇒ [tex]x = -8[/tex]
Therefore, x= -8 & correct option to solve the equation Three-fourths x = negative 6 for x in one step is option A i.e. Three-fourths (four-thirds) x = negative 6 (four-thirds).